2004
DOI: 10.1897/03-353
|View full text |Cite
|
Sign up to set email alerts
|

Role of source matrix in the bioavailability of polycyclic aromatic hydrocarbons to deposit‐feeding benthic invertebrates

Abstract: The bioavailability of polycyclic aromatic hydrocarbons (PAHs) to benthic organisms is complicated by the variety of ways that they are introduced to coastal waters (dissolved, as nonaqueous phase liquids, and tightly bound to soot, coal, tire rubber, and eroded shale). In order to better understand the controlling variables that affect chemical and biological availability of PAHs, a study was conducted in which three deposit-feeding infaunal benthic invertebrate species (Cirriformia grandis, Clymenella torqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
(74 reference statements)
0
11
0
1
Order By: Relevance
“…Higher Z S values for this sediment relative to Lake Conjola are consistent with this sediment having a greater sorptive affinity (Table 1). Sediments rich in black carbon are likely to have a smaller pool from which organisms can accumulate hydrophobic contaminants, and several studies have identified that soils and sediments rich in this material can be less toxic than similar, although diagenetic carbon‐rich, geosorbents [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Higher Z S values for this sediment relative to Lake Conjola are consistent with this sediment having a greater sorptive affinity (Table 1). Sediments rich in black carbon are likely to have a smaller pool from which organisms can accumulate hydrophobic contaminants, and several studies have identified that soils and sediments rich in this material can be less toxic than similar, although diagenetic carbon‐rich, geosorbents [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Higher BSAF values are considered indicative of biomagnification for very hydrophobic chemicals, substantial intake of food or sediment particles, or both (Thomann 1989). BSAF values for chemicals in sediments containing black carbon also may be depressed due to bioavailability constraints (Cornelissen et al 2005; Koelmans et al 2006), and other source matrices can influence bioavailability (Rust et al 2004). For both aspects, model parameterizations are available that can be applied to help interpret BSAF data in depth (Moermond et al 2005; Moermond, Traas, et al 2007).…”
Section: Screening Assessmentmentioning
confidence: 99%
“…La mayoría de los contaminantes orgánicos (HAPs, plaguicidas, PCBs), debido a su naturaleza hidrofóbica, se asocian fuertemente a las partículas del sedimento y a la materia orgánica (Kukkonen & Landrum, 1996), por lo tanto las propiedades de la superficie de las partículas y la proporción de materia orgánica se relacionan con la biodisponibilidad de los mismos (Davies et al, 1999;Haitzer et al, 1999;Verrengia Guerrero et al, 2003;Kukkonen et al, 2003;Rust et al, 2004;Sormunen, 2008).…”
Section: Figura I1: Esquema General De Las Fuentes De Contaminación unclassified